Fiqh Issues in the Border Areas of West Kalimantan - Hamka Siregar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
The less prosperous condition of the community in the Indonesia-Malaysia border area in the province of West Kalimantan has resulted in several problems including those related to fiqh, such as the sale and purchase of illegal goods from Malaysia, the phenomena of illegal migrant workers from Indonesia, human trafficking, transnational marriages, double identity cards, etc. In the perspective of fiqh, there is no ban on trading between people of different nationalities. In the legislative provisions, all citizens are bound not to commit illegal trade. On the other hand, the cases of double identity cards, transnational marriages, and the issue of migrant workers, in fact, are against the fiqh. However, in the context of citizenship, people should follow the provisions of the prevailing legislation. These fiqh issues have motivated the author to analyze them from the perspective of fiqh. Hopefully, we can get a picture of the fiqh problems in the Indonesia-Malaysia border area and find solutions to them.DOI: 10.15408/sdi.v23i2.2654